Influence of Unloading Conditions of Confining Pressure on the Compressive Strength and Permeability of Deep Mudstone. (9th March 2021) - Xin, Tianyu; Sun, Yashengnan; Wang, Junguang; Sun, Weiji
Abstract : To investigate the compressive strength and permeability of deep mudstone under stress disturbance, a triaxial rheometer is used to conduct seepage experiments on mudstone specimens with different buried depths under triaxial compression and unloading conditions. The experimental results show that the compressive strength of mudstone specimen with a depth of 1000 m is much lower than that of specimen with a depth of 200 m, and the compressive strength of mudstone increases with the increase in confining pressure. Under constant axial pressure and unloading of the confining pressure, the mudstone with a depth of 200 m exhibits brittle failure, and the strain fluctuates in a pointwise manner with the increase in axial stress. In this case, the mudstone with a depth of 1000 m exhibits a transition from brittle failure to ductile failure, and the strain fluctuates linearly with the axial stress. Further, when the volumetric strain change reaches 0.01, it shows an oblique " Z " fluctuation. During the initial stage of unloading of confining pressure, the permeabilities of both the mudstone specimens (with depths of 200 and 1000 m) decrease gradually. As the confining pressure is unloaded, the permeability of mudstone with a depth of 1000 m increases. Until the specimen is completely destroyed, the permeability of mudstone increases rapidly. Overall, this study can serve as a useful reference for analyzing the engineering disasters associated with deep rock mass, tunnel ventilation, and gas storage.